2006
DOI: 10.1038/nbt1192
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive metabolic profiling and phenotyping of interspecific introgression lines for tomato improvement

Abstract: Tomato represents an important source of fiber and nutrients in the human diet and is a central model for the study of fruit biology. To identify components of fruit metabolic composition, here we have phenotyped tomato introgression lines (ILs) containing chromosome segments of a wild species in the genetic background of a cultivated variety. Using this high-diversity population, we identify 889 quantitative fruit metabolic loci and 326 loci that modify yield-associated traits. The mapping analysis indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
633
6
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 696 publications
(680 citation statements)
references
References 44 publications
31
633
6
10
Order By: Relevance
“…Consistent with this idea, cells in developing fruit were shown to contain photosynthetically active chloroplasts (Piechulla et al, 1987), suggesting that photosynthesis may provide a significant contribution to both metabolism and growth of the fruit organ. This hypothesis is further supported by global transcriptomic profiling of transgenic lines altered in auxin response owing to down-regulation of SlIAA9, an Aux/IAA gene, which revealed that the activation of photosynthesis-related genes is a major phenomenon in developing tomato fruit (Schauer et al, 2006;Wang et al, Figure 6. Expression profile of SlAGPase genes in wild-type and ASL1 tomato fruits.…”
Section: Discussionmentioning
confidence: 58%
“…Consistent with this idea, cells in developing fruit were shown to contain photosynthetically active chloroplasts (Piechulla et al, 1987), suggesting that photosynthesis may provide a significant contribution to both metabolism and growth of the fruit organ. This hypothesis is further supported by global transcriptomic profiling of transgenic lines altered in auxin response owing to down-regulation of SlIAA9, an Aux/IAA gene, which revealed that the activation of photosynthesis-related genes is a major phenomenon in developing tomato fruit (Schauer et al, 2006;Wang et al, Figure 6. Expression profile of SlAGPase genes in wild-type and ASL1 tomato fruits.…”
Section: Discussionmentioning
confidence: 58%
“…Although only a fraction of the metabolic phenotype can be measured, due to the high connectivity in metabolic networks 34 , the profiles carry information about other unmeasured traits 41 . Regression-based analyses have shown that metabolite and enzyme activity profiles provide an integrative metabolic phenotype that is predictive of biomass 33,34,42,43 , heterosis 44 , and, to a lesser extent, abiotic stress tolerance in plants 45 .…”
Section: Resultsmentioning
confidence: 99%
“…Association mapping by GWAS is suitable for screening a large number of accessions for common variants within the population at relative high resolution (Huang et al, 2010;Huang and Han, 2012), while linkage mapping using artificial populations such as RILs and ILs is likely to be more powerful in identifying alleles with low frequency or small effects in the population (Fridman et al, 2004;Keurentjes et al, 2006;Schauer et al, 2006;Matsuda et al, 2012). Joint linkage and association mapping as illustrated in the study proved to be useful not just in cross-validating results from one another, but also complimenting each other in identifying new candidate loci (Luo, 2015).…”
Section: Discussionmentioning
confidence: 99%